Regulated expression of ADAMTS-12 in human trophoblastic cells: a role for ADAMTS-12 in epithelial cell invasion? - Alexander G Beristain (Public Library of Science (PLoS), 2011)
Metastatic carcinoma cells exploit the same molecular machinery that allows human placental cytotrophoblasts to develop an invasive phenotype. As altered expression levels of ADAMTS (ADisintegrin And Metalloproteinase with ThromboSpondin repeats) subtypes have been associated with cancer progression, we have examined the function and regulation of members of this gene family in epithelial cell invasion using cultures of highly invasive extravillous cytotrophoblasts and the poorly invasive JEG-3 cytotrophoblast cell line as model systems. Of the multiple ADAMTS subtypes identified in first trimester human placenta and these two trophoblastic cell types, only ADAMTS-12 was preferentially expressed by extravillous cytotrophoblasts. Transforming growth factor-β1 and interleukin-1β, two cytokines that promote and restrain cytotrophoblast invasion in vitro, were also found to differentially regulate trophoblastic ADAMTS-12 mRNA levels. Loss- or gain-of-function studies confirmed that ADAMTS-12, independent of its proteolytic activity, plays a specific, non-redundant role in trophoblast invasion. Furthermore, we demonstrated that ADAMTS-12 regulated cell-extracellular matrix adhesion and invasion through a mechanism involving the αvβ3 integrin heterodimer. This study identifies a novel biological role for ADAMTS-12, and highlights the importance and complexity of its non-proteolytic domain(s) pertaining to its function.